A bioluminescent probe for in vivo imaging of pyroglutamate aminopeptidase in a mouse model of inflammation. (1st July 2021) - Hu, Shilong; Chen, Xinxin; Qin, Xiaojun; Dong, Gaopan; Lin, Yuxing; Gai, Wenrui; Zhao, Hanqing; Ke, Bowen; Li, Minyong
Graphical abstract: Abstract: Pyroglutamate aminopeptidase (PGP) specifically cleaves the peptide bond of pyroglutamic acid linked to the N-terminal end of a polypeptide or protein. Previous studies showed that PGP was associated with several physiological processes and diseases especially those involving inflammation. Utilizing a 'caging' strategy, we designed and synthesized a bioluminescence probe (PBL ) with a limit-of-detection of 3.7 * 10 −4  mU/mL. In vivo imaging in a mouse model of inflammatory liver disease revealed that the probe has excellent sensitivity and selectivity and provides a powerful tool for studying the physiological and pathological processes involving PGP.